2000
DOI: 10.1046/j.1440-1746.2000.02323.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic analysis of stage II–III hepatocellular carcinoma showing early massive recurrence after liver resection

Abstract: Highly malignant HCC with extremely poor prognosis exhibits peculiar clinicopathologic characteristics, particularly histologic immaturity, and can be predicted by preoperative indicators such as markedly elevated tumor marker concentrations and condensed pooling on angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 31 publications
1
34
0
Order By: Relevance
“…This finding is particularly important because HCC invades vessel walls and metastasizes inside the liver, which is considered a major cause of death from the disease (29,30). It may be argued that the inhibitory effects of AS to CDC25A on cancer cell invasion may simply reflect reduced tumor cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is particularly important because HCC invades vessel walls and metastasizes inside the liver, which is considered a major cause of death from the disease (29,30). It may be argued that the inhibitory effects of AS to CDC25A on cancer cell invasion may simply reflect reduced tumor cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Tanaka and Izumi showed that postoperative adjuvant TACE improved the survival of HCC patients [28,29] . The patients selected in their clinical trials had advanced stages (TNM III or TNM IV) or characteristics of uncompleted encapsulated, intrahepatic metastasis, or vascular invasion which was thought to have a close relation with residual tumor and earlier massive recurrence [22,30] . For these patients postoperative adjuvant TACE played a role in earlier therapy of the residual tumor and could decrease the earlier recurrence and prolong survival.…”
Section: Discussionmentioning
confidence: 99%
“…As a predictive factor for recurrence after resection of HCC, the extratumor spreads was found to be more accurate than is any single invasiveness parameter such as Vp or IM [53] . The patients with macroscopic portal vein invasion, microscopic vascular invasion, intrahepatic metastasis, poor differentiation, pleomorphism, sarcomatous change, vascular lake, and angiographic condensed pooling were more frequently found to have extremely poor prognosis [54] . The prognosis of patients with lymph nodal metastasis from HCC is generally poor, even if hepatic resection with regional LN dissection is performed [52,55] .…”
Section: Venous Invasion and Intra-or Extrahepatic Spreadingmentioning
confidence: 99%